2020
DOI: 10.1101/2020.12.23.20245316
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Smoking and SARS-CoV-2 Impair Dendritic Cells and Regulate DC-SIGN Expression in Tissues

Abstract: SummaryThe current spreading novel coronavirus SARS-CoV-2 is highly infectious and pathogenic. In this study, we screened the gene expression of three SARS-CoV-2 host receptors (ACE2, DC-SIGN and L-SIGN) and DC status in bulk and single cell transcriptomic datasets of upper airway, lung or blood of smokers, non-smokers and COVID-19 patients. We found smoking increased DC-SIGN gene expression and inhibited DC maturation and its ability of T cell stimulation. In COVID-19, DC-SIGN gene expression was interestingl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 91 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…Nicotine has an important role in the regulation of ACE 2 receptors' immunomodulation, and this is shown in the fact that ex-smokers have a 25% increase in pulmonary ACE2 receptor expression over non-smokers. These findings revealed that former smokers were more susceptible to getting viruses and allowed them to enter their lungs [27]. Smoking has emerged as an independent risk not only for transmission but also for the severity of coronavirus disease 2019 (COVID-19).…”
Section: Covid-19 Primarily Targets Lung Epithelial Cells Causing Vir...mentioning
confidence: 99%
“…Nicotine has an important role in the regulation of ACE 2 receptors' immunomodulation, and this is shown in the fact that ex-smokers have a 25% increase in pulmonary ACE2 receptor expression over non-smokers. These findings revealed that former smokers were more susceptible to getting viruses and allowed them to enter their lungs [27]. Smoking has emerged as an independent risk not only for transmission but also for the severity of coronavirus disease 2019 (COVID-19).…”
Section: Covid-19 Primarily Targets Lung Epithelial Cells Causing Vir...mentioning
confidence: 99%
“…Nicotine has an important role in the regulation of ACE 2 receptors' immunomodulation, and this is shown in the fact that ex-smokers have a 25% increase in pulmonary ACE2 receptor expression over non-smokers. These findings revealed that former smokers were more susceptible to getting viruses and allowed them to enter their lungs [27]. Smoking has emerged as an independent risk not only for transmission but also for the severity of coronavirus disease 2019 (COVID-19).…”
Section: Covid-19 Primarily Targets Lung Epithelial Cells Causing Vir...mentioning
confidence: 99%